Enterprise Architecture sebagai Strategi Pengembangan Smart Village pada Dimensi Health Services - Khaerunisa Nur Ikrima; Asti Amalia Nur Fajrillah; Widyatasya Agustika Nurtrisha (SOTVI - Society of Visual Informatics, 2023)
The information technology utilization in the healthcare industry is crucial, considering that health is fundamental to the implementation of Sustainable Development Goals (SDGs). One aspect that needs improvement is the provision of public services at the village government level, using the concept of a smart village in healthcare services to enhance the SDGs value of the village. This research method utilizes the TOGAF ADM 9.2 framework, which consists of seven phases: Preliminary, Architecture Vision, Business Architecture, Information System Architecture, Technology Architecture, Opportunities and Solution, also Migration Planning. The design of the Smart Village Enterprise Architecture helps village governments improve their quality of life while achieving sustainable development in accordance with the Presidential Regulation of the Republic of Indonesia Number 111 of 2012.